Clinical outcome in patients treated with endoscopic submucosal dissection for superficial Barrett’s neoplasia - Chevaux, Jean Baptiste; Piessevaux, Hubert; Jouret-Mourin, Anne; Yeung, Ralph; Danse, Etienne; Deprez, Pierre H. (Endoscopy, 2015)
Background and study aims: The role of endoscopic submucosal dissection (ESD) in Barrett’s neoplasia is ill-defined, although it might provide a higher curative resection rate and better histologic assessment than endoscopic mucosal resection (EMR). We aimed to assess efficacy, safety, and long-term results of ESD.Patients and methods: A retrospective analysis was done of 75 consecutive patients with Barrett’s esophagus who underwent ESD between January 2007 and February 2014. ESD was performed for visible lesions that were multiple, larger than 15 mm, or poorly lifting, or suspected of submucosal infiltration. The primary end point was the rate of curative resection of carcinoma. Results: Median patient age was 68 years (interquartile range [IQR] 61 – 76), median follow-up was 20 months (IQR 8.5 – 37.5), and median maximum specimen diameter was 52.5 mm (IQR 43 – 71). En bloc resection rate was 90 % (66 /73), and rates of curative resection of carcinoma and high grade dysplasia/carcinoma were 85 % (47 /55) and 64 % (42 /66), respectively. G3 differentiation and invasion to greater than pT1m2 were observed in 25 % (14 /55) and 67 % (37 /55) of patients with adenocarcinoma, respectively. There were 5 early ( < 48 hours) adverse events (2 delayed hemorrhages and 3 perforations), all treated endoscopically. No ESD-specific death occurred. Esophageal strictures developed in 60 % of patients, all treated endoscopically. Additional treatment (median sessions 2 [IQR 2 – 3]) for residual Barrett’s esophagus were recommended to 62 % (42 /68). At latest follow-up, complete remission of neoplasia and intestinal metaplasia was found in 92 % (54 /59) and 73 % (43 /59) of patients, respectively. Conclusion: ESD appears to be safe and effective, with a high rate of curative resection of carcinoma. ESD should be considered for patients with Barrett’s neoplasia at risk of incomplete resection or poor pathologic assessment with conventional EMR.